Measurement of physical activity for public health purposes : validity and reliability of the International Physical Activity Questionaire(IPAQ) - Bohlmann, Isabelle Marie Therese (MRC/UCT RU for Exercise and Sport Medicine, 2017)
Physical inactivity is a well-recognized risk factor for chronic diseases of lifestyle and has been associated with an increased incidence of morbidity and mortality. Current recommendations for the "dose" of physical activity that may be regarded as "protective" for these chronic diseases are 30 minutes or more of moderate-intensity physical activity on most, or preferably all, days of the week. However, when quantifying physical activity, it is not clear which factors influence the reporting of moderate and vigorous activity levels. Even in the literature, there is lack of agreement on the energy expenditure corresponding to so-called 'moderate' and 'vigorous' physical activity. Background (study 1): Self- reported physical activity levels are inversely related to chronic disease risk factors. The strength of this association depends, in part, on quantifying the intensity of activity that may be regarded as 'moderate or vigorous', which may be confounded by individual and cultural perceptions of relative exercise intensity, age, fitness, height, and habitual levels of activity. Aim (study 1): The purpose of this study was to i) examine the individual and group differences in self-selected walking pace corresponding to symptoms used to describe moderate and vigorous intensity and ii) to determine factors that may be associated with these differences. Methods (study 1): A convenience sample of 63 women and 39 men were recruited (N=102). Subjects were asked to walk for six minutes on an indoor track at a pace they regard as 'moderate', rest until heart rate returns to pre-exercise levels, then walk at a pace they consider 'vigorous'. Habitual levels of energy expenditure (EE), maximal oxygen consumption (VO₂max) and% fat were also determined. Results (study 1): Mean self-selected walking pace for moderate activity levels was 5.54 km-h⁻¹ (95% Confidence Interval (C.I.): 5.40; 5.69), and corresponded to 58% of age-predicted maximum heart rate (%HR.max) (95% C.I.: 56; 60). Mean self-selected vigorous pace was 7.03 km·h⁻¹ (95% C.I.: 6.85; 7.20), at 72 % HR.max (95% C.I.: 69; 74). The %HR.max for both moderate and vigorous intensity physical activity fell within the ACSM recommendations (55- 69%HR.max for moderate intensity activities, and 70 - 89 % HR.max for vigorous intensity activities). Multivariate analysis revealed that the factors predicting self-selected walking speed were gender, age, VO₂max, % fat and habitual vigorous EE. The only significant predictor of moderate pace was VO₂max. Education, occupation and habitual moderate EE were not associated with walking speed or intensity. Conclusion (study 1): These results show that subjects could accurately differentiate absolute and relative walking intensities and understood what was meant by the terms 'moderate' and 'vigorous'. However, absolute pace and relative intensity may vary according to differences in gender, fitness, age, height, body fat% and habitual levels of vigorous activity. These factors are important to consider when prescribing exercise using descriptors such as "moderate" and "vigorous". Background (study 2): None of the various methods used to measure habitual physical activity in the general population have proven entirely satisfactory in terms of reliability and accuracy. A major problem is that no "gold standard" exists for the validation of various questionnaires that can be used in large sample population studies. Ongoing efforts to improve the validity and reliability of the measurement of physical activity by self-report will enable cross-cultural and international comparisons to examine secular trends. Aim (study 2): The second part of this study assessed the validity and reliability of a recently developed International Physical Activity Questionnaire (IPAQ) which was interviewer-administered in both a short and long version, and queried activity performed in a "usual" week. Methods (study 2): Urbanized subjects (N = 82) were selected from a wide range of educational, activity level and socio-economic backgrounds. The long version IPAQ was designed to quantify the average weekly time and energy expenditure spent in occupation, transport-related activities, household chores, and leisure time activities. The short version IPAQ was designed to measure total weekly moderate, vigorous, walking and sitting related activity. Test-retest reliability was reported as the intra-class correlation between calculated time and energy expenditure (METmin·w ⁻¹) in different questionnaire items determined from three IPAQ administrations. Validity was assessed using biometrical and physiological parameters as criterion measures (Computer Science and Applications. Inc. activity monitor counts, body mass index, estimated VO₂max, % fat). Results (study 2): Test-rest reliability coefficients for the long IPAQ ranged from r = 0.38 tor= 0.75, with the highest correlation coefficients obtained in work related activities, and the lowest in household chores. Test-retest reliability in the short IPAQ ranged from r= 0.32 tor= 0.71, with the highest correlations obtained for sitting and the lowest for total moderate activity. Criterion validity for CSA counts and total physical activity in the long IPAQ was r = 0.50 (P < 0.001), for CSA counts and total vigorous activity r = 0.35 (P < 0.01), and for CSA counts and total job activity r = 0.51 (P < 0.001). Measurement of reliability and validity in this South African population compared favourably to physical activity questionnaires used in other population studies. Conclusion (study 2): The IPAQ provides a relatively valid and reliable estimate of physical activity in this population. In evaluating the relationship between physical activity and morbidity, it is important to consider the accuracy and reliability of the tool used to measure self-reported activity. Failure to show an association may represent a real phenomenon, or may simply reflect the inability of the physical activity questionnaire used to detect true physical activity levels.